The Effect of Diamond Passing Training Model on Passing Accuracy in Soccer School Students - Ferdi Fahrus Syaehan; Imam Hariadi (Journal of Physical and Outdoor Education, 2025)
This study aims to determine the effect of diamond passing training model on passing accuracy in students at SSB Tunjung Sekar. Using a quantitative approach with a pre-experimental method, this study used a one group pretest-posttest design. The population and sample in the study were 20 SSB Tunjung Sekar students selected by simple random sampling through a lottery system. Data was collected using short passing test. Data analysis included normality test, homogeneity test, and paired sample T-test. The findings showed a significant increase in the mean score from 4.50 in the pre-test to 7.89 in the post-test. The significance value of 0.000 from the paired t-test shows a significant effect. It can be concluded that the diamond passing training model significantly improves the passing accuracy of SSB Tunjung Sekar students